Educational Management Using E-Learning to Maximize Learning Efficiency and Speed Up the Industrial Revolution 4.0 - Ahmad Qurtubi (STAI Hubbulwathan Duri, 2021)
Education is the key to increasing the quality of human resources. The rapid development of information technology has necessitated a shift in the educational paradigm. Based on the study of education policy, this study aims to determine how e-learning management can be used to achieve the effectiveness and acceleration of learning in today's 4.0 revolution era. This study uses a literature review as a method of data collection. Indonesia's e-learning policies are not clearly defined by law, according to the findings of an investigation.